Digitalisierung der Medienordnung 1. Berlin-Potsdamer Konferenz zu interdisziplinären Rechtsfragen - Schladebach, Marcus; Thiele, Alexander (Mohr Siebeck, 2023)
Digitalisation is fundamentally changing the media landscape. The first Berlin-Potsdam Conference on Interdisciplinary Questions of Law took a closer look at possible communication and efficiency gains on the one hand and realistic threats through hatespeech, fake news and potential copyright infringements on the other hand. The lectures held at the conference are presented in this volume.
PublicationDate: 20230510
Keywords: Urheberrecht -- Netzfreiheit -- Gesetz über den Rechtsschutz bei strafrechtlichen Ermittlungsverfahren -- Anonymität -- Fake News -- Social Media -- Unternehmerisches Ermessen -- Persönlichkeitsrechtsschutz -- new biographies -- Hate Speech -- Wahlsystem -- Social Participation -- Influencer-Marketing -- internationales Migrationsrecht -- Besonderes Verwaltungsrecht -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht